Codeveloping a community-based, peer-led psychosocial support intervention to reduce stigma and depression among people with tuberculosis and their households in Indonesia: a mixed-methods participatory action study - Ahmad Fuady; Mariska Anindhita; Matsna Hanifah; Arieska Malia Novia Putri; Artasya Karnasih; Feranindhya Agiananda; Finny Fitry Yani; Marinda Asiah Nuril Haya; Trevino Aristaskus Pakasi; Tom Wingfield (npj Primary Care Respiratory Medicine)
Abstract Evidence relating to peer support and community-based psychological and social (psychosocial) interventions to reduce stigma and depression among people with tuberculosis (TB) and their households is limited. This study aimed to engage with multisectoral stakeholders in Indonesia to co-develop a peer-led, community-based psychosocial intervention that is replicable, acceptable, and sustainable. We used a participatory action design and engaged key national, multisectoral stakeholders to ensure that the intervention co-design was relevant and appropriate to the TB health system and the sociocultural context of Indonesia. The co-design of the intervention evolved through four phases: (1) a scoping review to identify a long list of potential TB stigma reduction interventions; (2) a modified Delphi survey to define a shortlist of the potential interventions; (3) a national multisectoral participatory workshop to identify and pre-finalize the most viable elements of psychosocial support to distill into a single multi-faceted intervention; and (4) finalization of the intervention activities. The scoping review identified 12 potential intervention activities. These were then reduced to a shortlist of six potential intervention activities through a modified Delphi Survey completed by 22 multisectoral stakeholder representatives. At the national participatory workshop, the suitability, acceptability, and feasibility of the six potential intervention activities were discussed by the key stakeholders, and consensus reached on the final four activities to be integrated into the psychosocial support intervention. These activities consisted of: individual psychological assessment and counselling; monthly peer-led group counselling; peer-led individual support; and community-based TB Talks. In Indonesia, meaningful participation of multisectoral stakeholders facilitated co-design of a community-based, peer-led intervention to reduce TB stigma and depression amongst people with TB and their households. The intervention was considered to be locally appropriate and viable, and is being implemented and evaluated as part of the TB-CAPS intervention study.